Effect of disorder on the radiative coupling between distant quantum dots embedded in a photonic crystal dimer. (January 2016) - Vasco, J.P.; Gerace, D.; Guimarães, P.S.S.
Abstract: Quantifying the radiative coupling between distant quantum emitters can be relevant for applications in quantum information processing on chip. Here we focus on semiconductor quantum dots embedded in photonic crystal dimers formed by two nominally identical L3 cavities, and we show that the effective radiative coupling between them is relatively robust against non-perfect quantum dot positioning and also, to a smaller extent, to structural disorder in the photonic crystal. We show that the coupling between the quantum dots is enhanced at resonance with the dimer photonic modes and is proportional to the quality factors of these modes as long as the two cavities are strongly coupled. We find that, for the configuration where the L3 defects are aligned along the horizontal axis, the radiative coupling is almost two times larger than the values obtained in previous work. Highlights: We calculate the radiative coupling between two quantum dots in a photonic crystal. The coupling strength can be as high as 2.5 meV. The coupling is robust against structural disorder of the photonic crystal dimer. The coupling is robust also against disorder in the quantum dot positioning. These results are highly relevant for solving the issue of entangling distant qubits.